High-pressure glass formation of a series of 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide homologues. Issue 1 (4th December 2017) - Yoshimura, Yukihiro; Takekiyo, Takahiro; Koyama, Yoshihiro; Takaku, Mayumi; Yamamura, Misaho; Kikuchi, Natsumi; Wakabayashi, Daisuke; Funamori, Nobumasa; Matsuishi, Kiyoto; Abe, Hiroshi; Hamaya, Nozomu
Abstract : [C n mim][TFSI] resists external pressure and retains the local liquid structure, as if a sponge absorbs a stimulus. Abstract : We investigated the stability of the liquid phase of a series of 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C n mim][TFSI]) homologues with different alkyl chain lengths for 3 ≤ n ≤ 10 at room temperature. We found that all [C n mim][TFSI] samples ( n = 3–10) formed a glassy state when pressure was applied. Intriguingly, the glass transition pressure ( p g ) slightly increases up to n = 5, reaches a plateau at n ≧ 8, and increases again at n = 10. This is completely different from the high-pressure glass formation of [C n mim][BF4 ], where the p g decreases as n increases. We discussed the local structural changes occurring in [C n mim][TFSI] in view of the conformational changes of the cation and anion, and small-angle X-ray scattering data. It seems that [C n mim][TFSI] is resistant to external pressure and retains its local liquid structure by conformational adjustments of the cation and anion.